Nondestructive passivation of the TiO2 electron transport layer in perovskite solar cells by the PEIE-2D MOF interfacial modified layer. Issue 22 (19th May 2021) - Ji, Jun; Liu, Benyu; Huang, Hao; Wang, Xinxin; Yan, Luyao; Qu, Shujie; Liu, Xin; Jiang, Haoran; Duan, Mingjun; Li, Yingfeng; Li, Meicheng
Abstract : The nondestructive modification of the PEIE-2D MOF interfacial modified layer improves the efficiency and stability of perovskite solar cells. Abstract : The industrialization of perovskite solar cells (PSCs) is based on the development of efficiency and stability. Here, a composite film of a polyethylenimine ethoxylated (PEIE) and tellurophene-based two-dimensional metal–organic framework (2D MOF) was introduced to realize the nondestructive passivation of TiO2 . This interfacial layer can not only realize the effective passivation of TiO2, but can also further improve the morphology of the perovskite film. After the modification of the PEIE-2D MOF composite film, the morphology and crystallinity of the perovskite film are greatly optimized, the trap states in the TiO2 layer are reduced, and the electron transport in the device is enhanced, thus finally achieving highly efficient and stable FA0.25 MA0.75 PbI3 PSCs with a maximum efficiency of 22.22%. It was demonstrated that the reduced trap states and the smooth surface of the TiO2 electron transport layer are the reasons for the high performance of modified PSCs. This method provides a new way for improving the interface state to achieve highly efficient and stable PSCs.